Participatory teacher-child interaction in advancing teaching coding and robotics in pre-primary education - Korkeaniemi Arttu; Lindfors Eila; Tanhuanpää Saija; Luukka Emilia (Technology, Environmental, Mathematics and Science (TEMS) Education Research Centre, Faculty of Education, University of Waikato, 2025)
Teacher-child interaction (TCI) and children’s participation has been propounded as a factor in enhancing children’s learning in formal learning settings, especially in pre-primary education. Consequently, learning basic skills in coding and robotics at an early age is necessary for constructing a knowledge base applicable in later studies. In the current study, TCI and children’s participation is seen advancing young learners’ (children of six years old) technology education. The theoretical framework applied in this study is the participatory teacher-child interaction model which is based on earlier research. The model consists of three domains: emotional support, classroom organisation, and participatory instructional support. These domains are further divided into specific dimensions. The focus of the study is to recognise which domains and dimensions of TCI are recognised in teaching coding and robotics. Secondarily, the study focuses on which characteristics of participatory teacher-child interaction are implemented when teaching coding and robotics. The qualitative video data were collected from six pre-primary education groups. Participants in the data (N=84) included 10 pre-primary education teachers and 74 young learners. Data were analysed with the content analysis. The results indicate classroom management as the main domain in TCI. The results also show that within classroom organisation, the dimensions of dealing with disruption and clarity of the programme of action are emphasised the most by teachers. As a result, putting effort into classroom organisation decreases participatory TCI in teaching coding and robotics. On the contrary, the teachers who support participatory TCI place more emphasis on emotional support and participatory instructional support, and act as more competent in teaching coding and robotics. Further research is needed to increase participatory TCI when teaching coding and robotics and to further add value to technology education.